Danish contractor’s application of the budget: Identifying purpose and comparing the budgets application level across job-position (Construction Economics and Building, 2024)
The construction contractors compete in a low-profit industry, this makes cost-performance and the accuracy and the application of the budget critical. Despite the importance of a highly effective cost management, no studies have currently examined how construction contractors apply the budget. To determine how construction contractors apply budgets, a questionnaire study has been conducted, which included 128 construction professionals, from varying job-positions of whom 67 completed it, corresponding to 52.3%. The participants rated their budget application with regards to six categories. Afterwards a statistical analysis was applied to identify ranks, differences and correlations between categories and across job-positions. A Kendall’s Tau correlation test revealed a positive correlation between the categories and their application, and a Friedman’s Rank test identified the following rank between the categories: Management, Control, Planning, Motivation, Communication and Coordination. Finally, a multinomial regression analysis revealed that a higher hierarchical position entails a higher application of the budget for all categories but motivation. The new insights to budget application are highly relevant for construction professionals carrying out cost-management. The findings can be to make a better fit between application and the presentation of the budget, thereby strengthening the managerial capability of the budget.